FLEXURAL BEHAVIOUR OF HIGH-PERFORMANCE FIBRE REINFORCED COMPOSITE-FILLED DOUBLE SKIN STEEL TUBE BEAMS WRAPPED CARBON FIBRE REINFORCED POLYMER SHEETS - AL-NINI, AHMED AHMED MOHSEN (2021)
Concrete filled-double skin steel tube (CFDST) members provide economic benefits by reducing self-weight, avoiding formwork and reinforcement bars as required in the traditional steel or concrete construction